EVALUATION OF LEARNING IN HIGH SCHOOL: SCIENTIOMETRIC INDICATORS - Benvindo de Souza, Cirlene (Revista Gênero e Interdisciplinaridade, 2024)
The assessment of learning of high school students has historically been limited to tests, which does not contribute to satisfactory cognitive levels. The present study aimed to analyze the literature on learning assessment aimed at secondary education in Brazil. We use scientometrics to track publications in the Web of Science and SciELO Citation Index databases. Basically, we seek to describe the patterns and trends of studies on this topic. The results highlight nine works published between 2011 and July 8, 2022. The researchers were from institutions in the Northeast, Southwest, North and South of Brazil. Disciplines such as Chemistry and Biology were those that developed the most research emphasizing the assessment of learning. Generally, researchers agreed on the importance of changing the way students are assessed. This research therefore encourages researchers to develop more studies on learning assessment in different school subjects. Furthermore, it is considered necessary to publish works in English so that there is greater circulation of information.